Caudal regression syndrome: A rare case report with review of the literature - V, HANSIKA; KARPUR, SANTOSH; Chander, D Mahesh (Indian Journal of Case Reports, 2022)
Caudal regression syndrome is a very rare neural tube disorder, in which the caudal vertebral column and spinal cord develop abnormally, causing substantial sensory and motor deficits, primarily in the legs. An abnormality in the spinal cord and nerve roots interacts with a section of lumbar, lumbosacral, or coccygeal spinal dysgenesis or agenesis. Here, we present a rare case of caudal regression syndrome in a 3-year-old male child who was brought to the pediatrics department with a serious complaint of urine dribbling since infancy. The infant was discovered with spina bifida, lumbar scoliosis, and cavus deformity in both feet during a routine health check. For which, a neurological opinion was taken. Plain X-ray revealed a partial sacral agenesis, MRI revealed anterior and posterior nerve roots of cauda equina divided into two bundles of fibers due to abnormal path. The lower back and both gluteal areas were underdeveloped. On the basis of radiological findings, a diagnosis of the syndrome was confirmed.